Function of Ovarian Tissue Grafts After Hypothermic Storage: Importance of Incubation Medium Composition - Kiroshka, Viktoria V.; Borodai, Kateryna O.; Trutaieva, Iryna A.; Pasieshvili, Nana Ðœ.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2019)
There were comparatively analyzed the morphology, endocrine function and folliculogenesis of mature and neonatal rat ovarian tissue grafts after hypothermic storage (HS) in the media with different composition. For research performance the following methods were used: heterotopic transplantation (study of ovarian tissue structure and function after HS); immunoassay (determining the concentration of sex hormones in plasma); morphological method (evaluation of tissue graft structure integrity after HS). The composition of incubation medium was experimentally proven to be a key factor in follicular development and endocrine function of ovarian tissue grafts of different stages of histogenesis after HS. It was found that the use of phosphate-buffered saline for HS significantly reduced the follicular pool and decreased the steroidogenic function of grafts in both mature and neonatal ovarian tissue. It was shown that when using the mannitol-containing solution for HS, the number of follicles (of different maturity degree and corpus luteum) and the endocrine function after ovarian tissue transplantation were comparable with those after fresh tissue transplantation. Probl Cryobiol Cryomed 2019; 29(1): 019â€“027 Â